Effects of synthetic hormones on breeding performance of Malaysian Mahseer (tor tambroides bleeker) in captivity - Nik Daud, Nik Md. Azuadi (2013)
Plasma sex steroids and breeding performances of Tor tambroides were studied. Filial generation one (F1) broodstocks (range body weight of 1.4 to 4.4 kg and range total length 43.9 to 73.0 cm) were used for artificial propagation. All females were given pretreatment with Ovaplant (23.4-44.9 μg kgˉ¹) for 6 weeks prior to induction. Selected synthetic hormones such as Ovaprim, Ovatide, Luteinizing hormone releasing hormone analogue (LHRHa), human chorionic gonadotropin (HCG),salmon gonadotropin releasing hormone analogue (sGnRHa/OvaRH), and carp pituitary extract (CPE) were used for the induction and the effect of hormones on breeding performance and larval quality of Tor tambroides were then evaluated. The best hormone from this induction was chosen to test its effectiveness at various dose levels in inducing ovulation of T. tambroides. In order to investigate what factors improve breeding performance of T. tambroides, an experiment was conducted to test the effect of dopamine antagonist domperidone (DOM) to accelerate the maturation and ovulation. Blood were collected from each treated female breeders at 0 h (prior to administration), 6, 12 and 24 h post injection. Plasma sample were analyzed for Testosterone (T) and 17β-estradiol (E2) concentrations using Enzyme Link Immunosorbent assay (ELISA). Ovulatory response, fertilization rate, hatching rate, and survival rate were determined and data for plasma steroid hormones were analyzed using analysis of varinace (ANOVA). The results showed that Ovatide (0.5 mL/kg BW) was the most reliable in inducing ovulation in female T. tambroides with highest (p < 0.05) breeding performance (egg and larval qualities) overshadowing the other tested hormones. Ovaprim (0.5 mL/kg BW) was next best followed by OvaRH (10 μg/kg BW). No ovulation occurred in the group treated with LHRHa (10 μg/kg BW), HCG (1000 I.U/kg BW) and CPE (10mg/kg BW). Ovatide was further chosen to test its effectiveness at various dose levels in inducing ovulation of T. tambroides. The result indicated that the total stripped eggs and fecundity were significantly highest (p < 0.05) when females were treated with Ovatide at a dose of 0.5 mL/kg BW compared to those administered at other levels, with values of percent fertilization, hatching, survival and normal larvae of 88, 84, 81 and 74%, respectively. Dose of higher or lower than 0.5 ml/kg BW Ovatide resulted in over ripening of ova and partial ovulation leading to production of higher deformed larvae. Sex steroids plasma concentration of T and E2 increased significantly in association with ovulation. The levels fluctuated and reached a peak at 12 h, then dropped dramatically at 24 post injection (PI). In contrast in the non-ovulated groups; LHRHa (10 μg/kg BW), CPE (10 mg/kg BW), HCG (1000 I.U /kg BW) and DOM (5 mg/kg BW), the sex steroids hormone concentration showed little increment after injection and rose at 12 h PI, then slowly dropped at 24 h PI. Changes in sex steroids hormone level after hormone induction lead to vitellogenesis, oocyte development and ovulation in female breeders. This study will provide an insight into sex hormone steroids variations during oocyte development and these results provide important basic information and possible use of plasma parameters as predictive factors of the success of hormonally induced ovulation in T. tambroides in captivity.